2009
DOI: 10.1109/tit.2008.2011524
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishability of Quantum States by Separable Operations

Abstract: Abstract- (2005)]. Notably, we obtain an explicit construction of indistinguishable subspaces of dimension 7 (or 6) by considering a composite quantum system consisting of two qutrits (resp. three qubits), which is slightly better than the previously known indistinguishable bipartite subspace with dimension 8.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
83
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(91 citation statements)
references
References 36 publications
8
83
0
Order By: Relevance
“…We show that any 2 ⊗ n subspace is locally distinguishable. Combining with the previous results [4,12,13], we conclude that there is no locally indistinguishable m ⊗ n subspace if and only if m 2 or n 2. Our key techniques can be used to study the distinguishability of three-dimensional bipartite subspace which contains a product state.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…We show that any 2 ⊗ n subspace is locally distinguishable. Combining with the previous results [4,12,13], we conclude that there is no locally indistinguishable m ⊗ n subspace if and only if m 2 or n 2. Our key techniques can be used to study the distinguishability of three-dimensional bipartite subspace which contains a product state.…”
Section: Introductionsupporting
confidence: 84%
“…Watrous also proved that there is no 2 ⊗ 2 locally indistinguishable subspace, by directly employing the results from [11]. Winter's result [5] implies that the existence of bipartite subspace Q such that Q ⊗k is locally indistinguishable for any k. Duan et al generalized Watrous's result to the most general m ⊗ n systems for m = n and the multipartite setting, and found locally indistinguishable subspaces with smaller dimensions [12,13]. Most notably, it was shown that any subspace spanned by three-qubit UPB is locally indistinguishable, and there exists a three-dimensional * nengkunyu@gmail.com † runyao.duan@uts.edu.au ‡ mying@it.uts.edu.au three-qubit locally indistinguishable subspace [13].…”
Section: Introductionmentioning
confidence: 99%
“…This resolves an open question raised in [DFXY09]. We also show that every unextendable product set together with one extra pure state orthogonal to every member of the unextendable product set is not perfectly discriminated by separable measurements.…”
Section: Overview Of Resultssupporting
confidence: 62%
“…According to Naimark's theorem, any non-projective measurement can be realized by a projective measurement on an extended Hilbert space. However, if a 2D non-projective measurement has more than two POVM operators, then so does the corresponding projective measurement, and such a measurement often cannot be realized by LOCC [16][17][18]. Thus, this approach cannot directly answer the question.…”
Section: Introductionmentioning
confidence: 99%